Nb-containing non-equiatomic ratio hypoeutectic high-entropy alloy and preparation method thereof

CN118291884BActive Publication Date: 2026-10-30CHINA THREE GORGES UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410315629.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-19
Publication Date
2026-10-30
Estimated Expiration
2044-03-19

AI Technical Summary

Technical Problem

[0004]目前,高熵合金已经展现出一定的性能优势,如研究最为广泛的CoCrFeNi系FCC体系,具有高延性、低温断裂韧性、耐腐蚀性和热稳定性,但是由于构成元素多为Co、Cr、Fe、Mn、Ni等过渡族元素,导致FCC体系高熵合金的强度较低

Benefits of technology

1、本发明通过合理的元素选择以及成分调整,设计了一种含Nb非等原子比亚共晶高熵合金。CoCrFeNi系合金具有单一的FCC相,其中的Co、Cr、Ni等元素都能提高材料的抗腐蚀性能,当引入Nb元素后,合金生成了具有HCP结构的Laves相,同时由于Nb元素具有较大原子半径,固溶在基体中进一步加剧了合金的晶格畸变,从而提高了合金的强度。本发明所述合金具有较好的抗腐蚀性能并且同时兼具强度与塑性,是一种综合性能优良的高熵合金。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118291884B_ABST
    Figure CN118291884B_ABST
Patent Text Reader

Abstract

The application provides a Nb-containing non-equiatomic ratio eutectoid high-entropy alloy and a preparation method. a Cr b Fe c Ni d Nb e , 25≤a≤30, 20≤b≤25, 35≤c≤40, 4≤d≤5 and 0<e≤8, and a+b+c+d+e=100. The Co, Cr, Fe, Ni and Nb metal elements are deoxidized, weighed according to the molar ratio and mixed in a certain order, then placed in a vacuum arc furnace, filled with high-purity protective gas argon, and then arc melting is carried out, the molten alloy liquid is stirred uniformly, the alloy ingot is cooled and turned over; after repeating the melting for 6 times, the high-entropy alloy ingot is obtained. The high-entropy alloy composition is determined by simple thermodynamic phase diagram calculation, the Nb-containing non-equiatomic ratio eutectoid high-entropy alloy has FCC phase and Laves phase at room temperature, can play multiple strengthening effects of high-entropy alloy, such as solid solution strengthening, precipitation strengthening, fine-grain strengthening and the like, so that the hardness, compressive strength, plasticity and corrosion resistance of the high-entropy alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials, and in particular to a method for preparing Nb-containing non-isoatomic hybrid high-entropy alloys. Background Technology

[0002] High-entropy alloys, also known as multi-principal-element alloys, contain five or more elements, breaking away from the traditional single-principal-element composition design concept. In the late 18th century, Professor Cantor's team first experimentally prepared Co. 20 Cr 20 Fe 20 Mn 20 Ni 20 A high-entropy alloy with an equiatomic ratio and a single-phase face-centered cubic (FCC) structure was developed. Experiments verified that this multi-principal-equal-atomic-ratio alloy possesses a stable single-phase crystal structure. However, high-entropy alloys with single-phase structures often fail to meet the performance requirements of material applications. Furthermore, the limitation of the equiatomic ratio restricts the range of elemental adjustments in equiatomic-ratio alloy systems, making it impossible to accurately improve alloy properties by altering the atomic ratio. Moreover, when precious metals are involved, the manufacturing cost increases significantly. This hinders its large-scale application in materials engineering.

[0003] To address the aforementioned issues, Professor Lu Yiping of Dalian University of Technology proposed the concept of eutectic high-entropy alloys in 2014 and successfully prepared AlCoCrFeNi eutectic high-entropy alloys with FCC and B2 phases. Since then, the design methods and systems of eutectic high-entropy alloys have been continuously developed and expanded. However, high-entropy alloys containing hypoeutectic structures are still rarely reported. Due to the interlocking and nesting of phases in hypoeutectic alloys, a network structure is formed, which makes the same principal component hypoeutectic composition exhibit superior mechanical properties compared to eutectic composition alloys. For example, the AlCoCrFeNi alloy reported in the literature Lu YP, Gao XZ, Jiang L, et al. Directly cast bulk eutectic and near-eutectic high entropy alloys with balanced strength and ductility in a wide temperature range [J]. Acta Mater, 2017, 124: 143-150. 2.2 Hypoeutectic high-entropy alloys exhibit superior strength and ductility compared to AlCoCrFeNi. 2.1Eutectic high-entropy alloys. Moreover, compared to eutectic high-entropy alloys, hypoeutectic high-entropy alloys with some primary FCC phases exhibit better strength-ductility matching. Furthermore, Pradeep et al. from the Max Planck Institute in Germany proposed the concept of non-equiatomic-ratio high-entropy alloys, further expanding the high-entropy alloy system. Research has shown that a well-designed non-equiatomic-ratio high-entropy alloy not only maintains the same crystal structure as the equiatomic-ratio alloy, but also offers a wider range of elemental adjustments, providing more possibilities for microstructure improvement and mechanical property control, thus giving it broad application potential in materials engineering.

[0004] Currently, high-entropy alloys have demonstrated certain performance advantages. For example, the most widely studied CoCrFeNi-based FCC system exhibits high ductility, low-temperature fracture toughness, corrosion resistance, and thermal stability. However, due to the predominantly transition elements such as Co, Cr, Fe, Mn, and Ni, the strength of FCC-based high-entropy alloys is relatively low. Therefore, adding strengthening elements, such as refractory elements like Ti, Nb, Ta, and Mo, to CoCrFeNi-based high-entropy alloys with the FCC phase is one effective way to improve their mechanical properties and corrosion resistance. Among these, Nb has a lower elastic modulus, melting point, and density compared to other refractory elements. Adding Nb to CoCrFeNi-based high-entropy alloys generates a Laves phase, which acts as a second-phase strengthening agent. Furthermore, due to Nb's large atomic radius, it can dissolve in the matrix, further exacerbating lattice distortion and thus increasing the alloy's strength. Therefore, designing a non-isoatomic subeutectic high-entropy alloy containing Nb has promising engineering application prospects. Summary of the Invention

[0005] Of the high-entropy alloys reported so far, non-equiatomic designs often fully leverage their various strengthening effects. However, high-entropy alloys with FCC phases suffer from low strength and hardness. This invention provides a design concept and preparation method for Nb-containing non-equiatomic eutectic high-entropy alloys. By introducing Nb into a CoCrFeNi alloy containing the FCC phase, a second phase, the Laves phase, is obtained, achieving synergistic strengthening through dual-phase synthesis. This results in high corrosion resistance while simultaneously possessing strength and ductility, thus showing broad application prospects in engineering fields.

[0006] To achieve the above objectives, the technical solution adopted by this invention is: a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloy, with the general formula Co. a Cr b Fe c Ni d Nb eIn the chemical expression, a, b, c, d, and e represent the molar percentages of the corresponding elements, where 25 ≤ a ≤ 30, 20 ≤ b ≤ 25, 35 ≤ c ≤ 40, 4 ≤ d ≤ 5, and 0 < e ≤ 8, and a + b + c + d + e = 100.

[0007] A method for preparing a high-entropy Nb-containing non-isoatomic hypoeutectic alloy comprises the following steps: Step 1, Grinding: Use different grades (240#, 400#, 600# and 800#) of SiC sandpaper to grind the surface of Co, Cr, Fe, Ni and Nb with a purity greater than 99.9% (mass fraction) of metallic raw materials to remove the oxide scale and impurities on the surface; Step 2, Cleaning: Place the polished metal elemental raw materials Co, Cr, Fe, Ni and Nb into separate containers, pour in ethanol, perform ultrasonic cleaning, and after thorough drying, place them into sealed bags for later use. Step 3, Ingredient Preparation: Weigh the required raw materials Co, Cr, Fe, Ni, and Nb according to the general formula. Step 4, Feeding: Place the raw materials Co, Cr, Fe, Ni and Nb prepared in step 3 into a water-cooled copper crucible, and place the pure titanium used for oxygen measurement and oxygen absorption into another water-cooled copper crucible. Step 5, Smelting: Place Co, Cr, Fe, Ni, and Nb into a water-cooled copper crucible in a vacuum arc melting furnace, and place the pre-prepared Ti ingot into another water-cooled copper crucible; close the furnace door and evacuate to 2.8 × 10⁻⁶. -3 ~3×10 -3 After Pa, high-purity argon gas is introduced in reverse to -0.06 to -0.05 MPa; after arc initiation, Ti ingots are first melted, and then alloy raw materials are melted to obtain hypoeutectic high-entropy alloys containing Nb.

[0008] Furthermore, during ultrasonic cleaning, the metallic raw material is cleaned three times, with each cleaning cycle lasting 3 minutes.

[0009] Furthermore, when weighing the elemental raw materials, the total mass of each alloy ingot is 40g, and the weighing is carried out using an electronic balance according to the general formula, with a weighing error of ±0.001g.

[0010] Furthermore, when placing elemental raw materials, Nb is placed at the bottom of the water-cooled copper crucible, while other elemental metal raw materials are placed on top of Nb in order of increasing melting point, namely Ni, Co, Fe and Cr, to ensure that each elemental metal is fully heated during smelting.

[0011] Furthermore, when smelting Ti ingots, smelt for 3-5 minutes to remove excess oxygen as much as possible; when smelting alloy raw materials, repeatedly turn and smelt 3-6 times, with each smelting time being 2-3 minutes.

[0012] Compared with the prior art, the present invention has the following advantages: 1. This invention designs a Nb-containing non-isoatomic hypoeutectic high-entropy alloy through reasonable element selection and composition adjustment. CoCrFeNi alloys possess a single FCC phase, where elements such as Co, Cr, and Ni enhance corrosion resistance. Upon introduction of Nb, the alloy forms a Laves phase with an HCP structure. Furthermore, due to Nb's large atomic radius, its solid solution within the matrix further exacerbates lattice distortion, thereby increasing the alloy's strength. The alloy described in this invention exhibits excellent corrosion resistance while simultaneously possessing both strength and ductility, making it a high-entropy alloy with superior overall performance.

[0013] 2. The high-entropy alloy of this invention realizes the design of high-entropy alloys with non-equiatomic ratios. The Nb-containing hypoeutectic high-entropy alloy is composed of FCC phase and Laves phase; 3. The high-entropy alloy of the present invention exhibits good strength, hardness, plasticity, and corrosion resistance. It can be seen that without the addition of Nb, the alloy has good plasticity, but this is severely mismatched with its strength. With the addition of Nb, while plasticity is improved, the compressive strength of Nb1 is also increased to a certain extent, achieving a certain balance between strength and plasticity. The strain and strength of Nb2 are much greater than those of Nb0 without Nb, and the strength of the alloy is greatly improved, reaching over 1400 MPa, more preferably over 1600 MPa, more preferably over 1700 MPa, and more preferably over 1800 MPa. The plastic strain can reach 29% or more, more preferably 35%, more preferably 40% or more, and more preferably 47% or more. In some preferred embodiments, achieving a strength of over 1600 MPa and a strain of 47% or more is extremely difficult, achieving the optimal effect for both. Although Nb6 sacrifices a small amount of ductility, its compressive strength is the highest among the alloy compositions studied, reaching 1803.3 MPa. Simultaneously, the electrochemical corrosion potential parameters of this alloy were obtained using Tafel curve characteristics. With increasing Nb content, the corrosion potential of the alloy shows an increasing trend, increasing from -0.61V for Nb1 to -0.51V for Nb6; however, when the Nb content further increases to Nb8, its corrosion potential decreases (to -0.65V). In summary, the high-entropy alloy of this invention exhibits good corrosion resistance and a high strength-ductility balance.

[0014] 4. The high-entropy alloy provided by this invention has excellent mechanical properties, a simple preparation process, strong safety, and excellent engineering application potential. Attached Figure Description

[0015] Figure 1 This is an experimental flowchart of the high-entropy alloy described in this invention.

[0016] Figure 2 This is the X-ray diffraction pattern of the high-entropy alloy described in this invention.

[0017] Figure 3 This is a metallographic diagram of the high-entropy alloy described in this invention.

[0018] Figure 4 This is the polarization curve of the high-entropy alloy described in this invention in a 3.5wt% NaCl solution.

[0019] Figure 5 This is a room temperature compressive stress-strain curve of the high-entropy alloy described in this invention.

[0020] Figure 6 This is a microscopic Vickers hardness variation diagram of the high-entropy alloy described in this invention. Detailed Implementation

[0021] To facilitate understanding of the present invention, the invention will be described more fully below in conjunction with specific embodiments, accompanying drawings, and preferred embodiments. It should be emphasized that the scope of protection of the present invention is not limited to the following specific embodiments.

[0022] All technical terms used in this document have the same meaning as commonly understood by those skilled in the art.

[0023] All the raw materials, reagents, instruments and equipment used in this invention can be purchased on the market.

[0024] Example 1: This embodiment discloses a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloys, whose general formula is (Co... 30 Cr 25 Fe 40 Ni5) 99 Nb1. The specific preparation method is as follows: Step 1, Grinding: Use different grades (240#, 400#, 600# and 800#) of SiC sandpaper to grind the surface of Co, Cr, Fe, Ni and Nb with a purity greater than 99.9% (mass fraction) in order to remove the oxide scale and impurities on the surface. Step 2, Cleaning: Place the polished elemental metals Co, Cr, Fe, Ni, and Nb into separate containers, pour in ethanol, and perform ultrasonic cleaning. During ultrasonic cleaning, the elemental metals are cleaned three times, with each cleaning cycle lasting 3 minutes. After thorough drying, place them in sealed bags for later use. Step 3, Batching: Calculate based on the molar percentage of a non-isoatomic hypoeutectic high-entropy alloy containing Nb. Using a total mass of 40g per alloy ingot as a base, weigh the required raw materials Co, Cr, Fe, Ni, and Nb according to the general formula using an electronic balance, with a weighing error of ±0.001g. Step 4, Feeding: Solid Nb is placed at the bottom of a water-cooled copper crucible in the electric arc melting furnace, while other elemental metals are sequentially placed on top of Nb in order of increasing melting point (Ni, Co, Fe, and Cr) to ensure that each element is fully heated during melting. Pure titanium, used for oxygen measurement and absorption, is placed in another water-cooled copper crucible. Step 5, Initial Vacuuming: The vacuum arc furnace undergoes initial vacuuming to achieve a vacuum level of 2.8 × 10⁻⁶. -3 ~3×10 -3 Pa, then fill with high-purity protective gas argon to -0.06~-0.05 Pa; Step 6, Secondary Vacuuming: The vacuum arc furnace undergoes a secondary vacuuming process to achieve a vacuum level of 2.8 × 10⁻⁶. -3 ~3×10 -3 Pa, then refill with high-purity protective argon gas to -0.06~-0.05 Pa.

[0025] Step 7: Begin Melting: Adjust the welding torch to a suitable position to successfully ignite the arc; after ignition, first melt the Ti ingot for 6 minutes to remove as much residual oxygen as possible from the furnace; then melt the alloy raw material, slowly increasing the current from about 20A to 300A, adjusting the welding torch position to stabilize the flame; after all the elemental metals have melted, stabilize the melting for 2 minutes, then turn off the arc; after the alloy cools and solidifies, flip it over and repeat the above operation 6 times to obtain a uniform microstructure, ultimately obtaining (Co) 30 Cr 25 Fe 40 Ni5) 99 Nb1 hypoeutectic high-entropy alloy button ingot.

[0026] Example 2 This embodiment discloses a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloys, whose general formula is (Co... 30 Cr 25 Fe 40 Ni5) 98 Nb2. The specific preparation method is as follows: The high-entropy alloy preparation method in this embodiment is the same as that in Example 1.

[0027] Example 3 This embodiment discloses a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloys, whose general formula is (Co... 30 Cr 25 Fe 40 Ni5) 96 Nb4. The specific preparation method is as follows: The high-entropy alloy preparation method in this embodiment is the same as that in Example 1.

[0028] Example 4 This embodiment discloses a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloys, whose general formula is (Co... 30 Cr 25 Fe 40 Ni5) 94 Nb6. The specific preparation method is as follows: The high-entropy alloy preparation method in this embodiment is the same as that in Example 1.

[0029] Example 5 This embodiment discloses a high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloys, whose general formula is (Co... 30 Cr 25 Fe 40 Ni5) 92 Nb8. The specific preparation method is as follows: The high-entropy alloy preparation method in this embodiment is the same as that in Example 1.

[0030] Comparative Example 1 Comparative Example 1 discloses a high-entropy alloy without Nb-type non-equiatomic ratio, with the general formula Co. 30 Cr 25 Fe 40 Ni5. The specific preparation method is as follows: The high-entropy alloy preparation method of Comparative Example 1 is the same as that of Example 1.

[0031] Comparative Example 2 Comparative Example 2 discloses a CoCrFeNiNb 0.5 A laser additive manufacturing method for high-entropy alloys. The specific preparation method is as follows: Step 1, Grinding: Use different grades (240#, 400#, 600# and 800#) of SiC sandpaper to grind the surface of Co, Cr, Fe, Ni and Nb with a purity greater than 99.9% (mass fraction) in order to remove the oxide scale and impurities on the surface. Step 2, Cleaning: Place the polished elemental metals Co, Cr, Fe, Ni, and Nb into separate containers, pour in ethanol, and perform ultrasonic cleaning. During ultrasonic cleaning, the elemental metals are cleaned three times, with each cleaning cycle lasting 3 minutes. After thorough drying, place them in sealed bags for later use. Step 3, Ingredients: Based on the molar percentage of a non-isoatomic hypoeutectic high-entropy alloy containing Nb, the required raw materials Co, Cr, Fe, Ni and Nb are weighed using an electronic balance according to the general formula, with a weighing error of ±0.001g. Step 4, Grinding: Place the cleaned and prepared elements into a ball mill and grind them evenly. Use a stainless steel ball mill jar, with a ball-to-material ratio of 10:1, a rotation speed of 300 r / min, and ball mill for 36 h to make the average particle size 45~105μm. Then dry in a vacuum dryer at 200℃ for 4 h to remove the moisture and ensure flowability. After that, pour the powder into the feed cylinder of the powder feeder for later use.

[0032] Step 5: Vacuuming: The equipment is evacuated, and then filled with high-purity protective gas argon to -0.010~-0.08 Pa; Step 6: Laser Sample Preparation: A 250mm × 100mm × 10mm 45# steel substrate was selected. The substrate surface was polished smooth using 240#, 400#, 600#, 800#, and 1000# sandpaper, respectively. After wiping with alcohol, the substrate was ready for use. A 30mm × 30mm × 10mm CoCrFeNiNb sample was prepared on the 45# steel under argon protection using a powder feeding method with a rated power of 1500W and a laser wavelength of 910~1050nm. 0.5 High-entropy alloy block sample.

[0033] 1. XRD (X-ray diffraction experiment) Cylindrical samples of Φ5mm×6mm were taken from the ingot using wire electrical discharge machining (EDM). The samples were polished with 240#, 400#, 800#, and 1200# sandpaper until the surface had a silvery-white luster, and then XRD tests were performed.

[0034] Figure 2 The X-ray diffraction pattern of the high-entropy alloy described in this invention shows that Examples 1-5, after the addition of Nb, consist of both the FCC phase and the Laves phase. The diffraction peak intensity of the FCC phase in Examples 1-5 is significantly higher than that of the Laves phase, indicating that the FCC phase remains the dominant phase of the alloy.

[0035] 2. Metallographic microscopic observation Cylindrical samples of Φ5mm×6mm were taken from the ingot using wire electrical discharge machining (EDM). After mounting, the samples were polished with 240#, 400#, 800#, 1200#, and 2000# sandpaper, and then polished. After observing no scratches under an optical microscope, the samples were etched with aqua regia in a 1:3 volume ratio of concentrated nitric acid and concentrated hydrochloric acid. After cleaning, the surface of the samples was dried, and the microstructure of the alloy was observed under an optical microscope.

[0036] Figure 3 The images show the microstructure of the high-entropy alloy described in this invention under an optical microscope. As can be seen from Examples 1-5, when the Nb content is 1%, a small amount of white Laves phase precipitates in the alloy; when the Nb content is 2%, the precipitated Laves phase exhibits a dendritic shape and is relatively uniformly distributed in the matrix; when the Nb content is 4%, the phases gradually connect to form a hypoeutectic network; when the Nb content is 8%, the interlamellar spacing gradually decreases, and the high-entropy alloy exhibits a typical dendritic crystal morphology; as the Nb content increases from 2% to 8%, the volume fraction of the Laves phase also increases from 2% to 32%, which is one of the main reasons for the increase in yield strength and compressive strength. Simultaneously, combined with... Figure 2 XRD analysis revealed that the microstructure of the alloys in Examples 1-5 was a hypoeutectic structure composed of FCC and Laves phases. From... Figure 3 Comparative Example 1 shows that Co without Nb 30 Cr 25 Fe 40 The Ni5 alloy exhibits a single FCC structure.

[0037] 3. Electrochemical corrosion experiment This experiment uses a three-electrode electrode system. A 10mm×10mm×10mm sample is placed in a 3.5wt% NaCl solution for electrochemical corrosion testing.

[0038] After powering on, stabilize the sample in the solution for 60 minutes. Once the open circuit potential has stabilized, set the parameters. The potential scan range is -2.0 to 0.5V, and the scan rate is 1mV / s.

[0039] Table 1 shows the polarization parameters of the high-entropy alloys of Examples 1-5 and the prior art in a 3.5 wt% NaCl solution.

[0040]

[0041] Figure 4 This is the polarization curve of the high-entropy alloy described in this invention in a 3.5 wt% NaCl solution. (Combined with...) Figure 4As shown in Table 1, the corrosion potential of the alloy increases with the increase of Nb content, from -0.61V for Nb1 to -0.51V for Nb6; however, when the Nb content is further increased to Nb8, its corrosion potential decreases to -0.65V.

[0042] 4. Room temperature compression test A Φ5mm×6mm cylindrical sample was taken from the ingot using wire electrical discharge machining (EDM) for compression testing. Compression rate: 0.36 mm / min. Table 2 shows the compressive strength and compressibility of high-entropy alloys in Examples 1-5 and the prior art.

[0043]

[0044] Figure 5 This is a room temperature compressive stress-strain curve of the high-entropy alloy described in this invention. (Combined with...) Figure 5 As shown in Table 2, the embodiments exhibit higher compressive strength, demonstrating a significant advantage over existing high-entropy alloys. Embodiment 4 exhibits the best compressive strength, with an alloy strength of 1803.3 MPa.

[0045] 5. Microhardness Test To reduce experimental error, each alloy was measured at least 10 times in different regions, discarding the highest value. The average value of the minimum and maximum values ​​is then taken as the microhardness value of the tissue.

[0046] Table 3 shows the Vickers hardness of comparative examples, some existing high-entropy alloys, and Examples 1-5.

[0047]

[0048] Figure 6 This is a Vickers hardness variation diagram of the high-entropy alloy described in this invention. (Combined with...) Figure 6 As shown in Table 3, the implementation The hardness of the examples is higher than that of the comparative examples and some existing high-entropy alloys.

[0049] Based on the above data, the overall performance of the embodiments is better than that of the comparative examples and the existing high-entropy alloys. Among them, the overall performance of Example 4 is the best, with a compressive strength of 1803.3 MPa, a hardness of 387.44 HV, and a corrosion potential of -0.51 V.

[0050] This invention, through reasonable element selection and composition adjustment, achieves an increase in the Laves phase content in the alloy as the Nb content increases, resulting in an increase in the Vickers hardness from the initial 244.06 HV to 442.73 HV; wherein (Co) 30 Cr25 Fe 40 Ni5) 94 The Nb6 high-entropy alloy has a compressive strength of 1803.3 MPa, a compression ratio of 29.6%, a hardness of 387.44 HV, and a corrosion potential of -0.51 V. It possesses high corrosion resistance while also exhibiting strength and ductility, indicating that this alloy has broad prospects for engineering applications.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-entropy alloy containing Nb-type non-isoatomic hypoeutectic alloy, characterized in that, The general formula is Co a Cr b Fe c Ni d Nb e In the chemical expression, a, b, c, d, and e represent the molar percentages of the corresponding elements, where 25≤a≤30, 20≤b≤25, 35≤c≤40, 4≤d≤5, and 1≤e≤8, and a+b+c+d+e=100.

2. A method for preparing a high-entropy Nb-containing non-isoatomic hypoeutectic alloy according to claim 1, characterized in that, The preparation steps are as follows: Step 1, Grinding: Grind the surfaces of Co, Cr, Fe, Ni and Nb raw materials with a purity greater than 99.9% by mass to remove the oxide scale and impurities on the surface; Step 2, Cleaning: Place the polished elemental metals Co, Cr, Fe, Ni and Nb into separate containers, pour in ethanol, perform ultrasonic cleaning, and after thorough drying, place them in sealed bags for later use. Step 3, Ingredient Preparation: Prepare the required raw materials Co, Cr, Fe, Ni, and Nb according to the molar ratio of each element. Step 4, Feeding: Place the raw materials Co, Cr, Fe, Ni and Nb prepared in step 3 into a water-cooled copper crucible, and place the Ti ingots used for oxygen measurement and oxygen absorption into another water-cooled copper crucible; Step 5, Initial Vacuuming: The vacuum arc furnace is used for initial vacuuming; then, argon gas is introduced as a protective gas. Step 6, Secondary Vacuuming: The vacuum arc furnace is subjected to a secondary vacuuming process and argon gas is introduced again as a protective gas. Before the melting begins, the Ti ingots in the water-cooled copper crucible are melted to remove the residual oxygen in the vacuum arc furnace. Step 7: Start melting: Adjust the welding gun to a suitable position to successfully ignite the arc; then melt the alloy raw material. After the alloy in the water-cooled copper crucible has completely melted, stabilize the melting and turn off the arc; after the alloy cools and solidifies, flip it over and repeat the above operation 3-6 times to obtain a homogeneous Nb-type non-isoatomic hypoeutectic high-entropy alloy.

3. The method for preparing Nb-containing non-isoatomic hypoeutectic high-entropy alloys according to claim 1, characterized in that, In step 2: During ultrasonic cleaning, the metallic raw material is cleaned 2-3 times, with each cleaning session lasting 2-3 minutes.

4. The method for preparing Nb-containing non-isoatomic hypoeutectic high-entropy alloys according to claim 1, characterized in that, In step 5: Initial vacuuming: The vacuum arc furnace undergoes initial vacuuming to achieve a vacuum level of 2.8 × 10⁻⁶. -3 ~3×10 -3 Pa; then fill with protective argon gas to -0.06~-0.05 MPa.

5. The method for preparing Nb-containing non-isoatomic hypoeutectic high-entropy alloys according to claim 1, characterized in that, In step 6: Secondary vacuuming: The vacuum arc furnace undergoes a secondary vacuuming process to achieve a vacuum level of 2.8 × 10⁻⁶. -3 ~3×10 -3 Pa, fill with protective argon gas to -0.06~-0.05MPa.

6. The method for preparing Nb-type non-isoatomic hypoeutectic high-entropy alloys according to claim 1, characterized in that, In step 7: Start melting: Adjust the welding gun of the electric arc furnace to a suitable position to successfully ignite the arc; Increase the current from 18-22A to 290-310A, and adjust the position of the welding torch to stabilize the flame. After the metal element is completely melted, stabilize the melting for 3-5 minutes and then turn off the arc. Turn the cooled alloy over and continue melting. Repeat the above operation 4-6 times to prepare the required high-entropy alloy ingot.

Citation Information

Patent Citations

  • NiCoCr-containing medium / high-entropy alloy with non-equal atomic ratio and preparation method thereof

    CN112725678A

  • Co-Ni-Cr-Fe-W series high-density and high-plasticity high-entropy alloy and preparation method thereof

    CN114395717A